MANAJEMEN PRODUKSI PROGRAM SIARAN “SHECANGKIR TEH PAGI” DI SHE RADIO 99,6 FM - Riyanti, Meyliana Eka; Winata, Muhammad Danu (Universitas Negeri Surabaya, 2024)
This research aims to explore the production management of the